Sengketa Mangaku Induak dalam Masyarakat Minangkabau: Studi Kasus di Dharmasraya - Tasbillah Syamyul; Abdul Alim (Lembaga Yasin AlSys, 2026)
The practice of mangaku induak in Minangkabau society, particularly in Dharmasraya, is a mechanism of social integration within the matrilineal kinship system that functions to provide social recognition to individuals who do not have a clear lineage within a clan. This study aims to examine the practice of mangaku induak, analyze the potential disputes it generates, and explain the mechanisms for resolving customary disputes in Minangkabau society. This study employed a qualitative approach with a socio-legal type. Data were collected through interviews, observation, and literature study and were then analyzed descriptively and qualitatively. The results showed that mangaku induak plays an important role in maintaining social order and cohesion, but it also has the potential to generate disputes, particularly regarding kinship status, inheritance rights to high-value ancestral property, and social recognition within society. These disputes are influenced by differences in understanding customary law, economic interests, lack of participation in deliberation, and social changes resulting from modernization. Dispute resolution is generally carried out through customary mechanisms, namely community deliberation, the role of ninik mamak, and the Nagari Customary Council (KAN), using a familial approach that emphasizes the restoration of social relations. The conclusion of this study affirms that mangaku induak remains relevant as a traditional practice in Minangkabau society but requires adaptive management so that it remains aligned with the dynamics of modern society without losing its fundamental values. These findings contribute to the development of studies on customary law and sociology of law, particularly in understanding the relationship between matrilineal kinship, social recognition, and customary dispute resolution.